Application of geostatistical methods in the development of landscape-adaptive land use - D. A. Ivanov (Аграрная наука Евро-Северо-Востока)
The article describes the ways of using statistical methods in agricultural geography. The use of analysis of variance in determining the influence of geocomplexes of various ranks on the yield of plants and other parameters of farms is shown. It was found that yield variability, soil acidity, the proportion of pastures and fallow lands are less than 30% determined by the characteristics of the natural environment of geosystems and the variability of plant nutrients, stony and marshy soil, and the share of haymaking by 30-50%. Other elements of the structural organization of enterprises are more than half determined by the peculiarities of the territories of different levels. The process of determining a set of crops should be based on knowledge of the variability of their yields within the types of agricultural landscapes, and, if possible, at lower taxonomic levels. The degree of development of agricultural landscapes and the average size of the contour of the land is determined even when analyzing the conditions of the macroenvironment. The use of track analysis allows to identify the factors of direct impact on the crops which are divided into "active" and "potential". It has been established that all types of agricultural landscapes of the Upper Volga region can be divided into two groups according to the number of active and potential factors: geocomplexes with a homogeneous lithogenic basis and landscapes on two-membered sediments. The latter are distinguished by a large number of active factors and a wide range of affected crops. The design of crop rotations should take into account an individual set of factors affecting the production process. The methodology for assessing the productivity of agricultural landscapes can be based on the use of its integral indicators. The systems of measures that increase the degree of realization of the potential productivity of agricultural landscapes for cereal grass stands have been determined. They are combined into three groups: 1. Adaptive placement of grass stands depending on the granulometric composition and the geological structure of the soil. 2. Adaptive placement of grass stands and drainage irrigation amelioration. 3. Adaptive placement of grass stands, water melioration and land management activities. Identified areas of distribution of these groups of activities in the Upper Volga region.